Phytochemical profile and biological activities of Caesalpinia coriaria extract: a review - Cipriano-Salazar, Moises; Salem, Mohamed Z. M.; Elghandour, Mona M. M. Y.; Selim, Shady; Lackner, Maximilian; Salem, Abdelfattah Z. M. (Frontiers in Veterinary Science, 2025)
Caesalpinia coriaria (Jacq.) Willd [syn.: Libidibia coriaria (Jacq.) Schltdl.], a member of the Fabaceae family and the Caesalpinioideae subfamily, is commonly known in Mexican vernacular as “cascalote“. Various botanical parts of this tree, such as leaves, pods, flowers, seeds, branches, and bark, have been studied due to their bioactivity and their astringent, antiparasitic, antiseptic, and anti-inflammatory properties. Extracts obtained from C. coriaria contain a wide range of bioactive compounds, including tannins, terpenoids, phenols, coumarins, quinones, flavonoids, saponins, carbohydrates, proteins, glycosides, cardiac glycosides, anthraquinones, steroids, and polyphenols. During the fattening phase in ruminants, these plant extracts may be used to reduce gastrointestinal parasitism, promote growth, and decrease drug residues in animal-derived products. This review aims to highlight the importance of the bioactivities of C. coriaria extracts and their active compounds. In vitro studies have demonstrated that the phenolic and flavonoid compounds present in this species inhibit bacterial growth by disrupting membrane integrity and enzymatic activity, often outperforming conventional antibiotics. In livestock production systems, the presence of pathogenic bacteria leads to significant economic losses; in this context, the use of polyphenolic compounds derived from C. coriaria may have a positive effect on animal productivity. Moreover, the extracts from this tree represent a promising source of bioactive compounds for various industrial applications.